Sagot :
Calculate
====================================
What is the sum of (+5) + (-1) =?
Answer:-
- [tex] \pink{\bold{4}}[/tex]
====================================
Solution:-
There is a+ in front of an expression in parenthesis, so the expression remains the same.
- [tex] \pink{\bold{(5 + ) + ( - 1)}}[/tex]
- [tex] \pink{\bold{5 + ( - 1)}}[/tex]
- [tex] \pink{\bold{5 - 1}}[/tex]
- [tex] \pink{\bold{4}}[/tex]
Therefore, the sum of (+5) + (-1) is 4.
====================================
#MakeBrainlyCommunityGreat